The Second Language Classroom Modes by Senior English Teacher at XYZ English Course in Surabaya - Vinna Veronica Yauwangsa; Henny PS Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2016)
This study is intended to find out the pedagogic goals, interactional features, and L2 classroom modes appeared in the fourth graders’ English classroom taught by senior English teacher. Conducting this study, I apply Walsh’s (2006, 2011) SETT (Self-Evaluation of Teacher Talk) framework. The data was collected for two meetings. The findings of this study show that among 18 pedagogic goals, 16 of them appeared. Moreover, all of 14 interactional features and all of four modes appeared in this study.Among the four modes, managerial mode was the most frequent mode (54.54%). In conclusion, the teacher could make the class interactive because she allowed learners to formulate responses for seconds so that learners could contribute more. Moreover, the teacher rarely completed learners’ contribution and corrected learners’ mistakes directly so that the learners might feel confident to contribute in the activities.